Government popularity and the economy first evidence from German micro data - Sören Enkelmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This is one of the first studies to estimate a popularity function at the micro-level. Using German micro-level data (GGSS/ALLBUS) for the years 1991, 1992, 1998, and 2008, we show that a positive assessment of the economy significantly improves government popularity while negative evaluations decrease satisfaction with the government. Voters take the (current and expected) national and personal economic situation into account. We find no evidence for a grievance asymmetry, i.e. voters punish the government for a bad economy but also reward them in good times. Finally, we show that popularity functions are only very crude proxies for vote functions, with the latter being mostly driven by party identification.
Keywords: D72; H11; 330; vote function; popularity function; micro data; Germany